Seed Germination Studies on Three Predominant Tree Species of Southern Uttar Pradesh - Misra, C M; Singh, S L (Annals of Arid Zone, 2016)
The paper deals with the germination behaviour and the relative salt tolerance of babul (Acacia arabica), khair (Acacia catechu) and siris (Albizzia lebbek) at the Forest Research Laboratory, Kanpur. These species have been recognised as useful for industrial and important domestic purposes. The shape index determinations, various pre-treatments for sowing of the seeds alongwith the relative salt tolerance studies were conducted under nursery and laboratory conditions. The study reveals that if the seeds are treated before sowing, germination and seedling emergence of the species are enhanced. The germination of these species were also studied under various salinity levels and tolerance ranges were worked out for all the three species.